Respuesta :
[tex]y=e^{mx}\implies y'=me^{mx}[/tex]
[tex]y'+6y=0\iff me^{mx}+6e^{mx}=(m+6)e^{mx}=0\implies m=-6[/tex]
So one solution to the ODE is [tex]y=e^{-6x}[/tex].
[tex]y'+6y=0\iff me^{mx}+6e^{mx}=(m+6)e^{mx}=0\implies m=-6[/tex]
So one solution to the ODE is [tex]y=e^{-6x}[/tex].
Answer:
m = -6
Step-by-step explanation:
Suppose we have an differential equation in the following format:
ay' + by = 0
The differential equation has the following equivalent polynomial
ar + b = 0.
The root of the polynomial is a value of m so that the function y = e^(my) is a solution of the equations.
In this problem, we have that:
y' + 6y = 0
The polynomial is
r + 6 = 0
r = -6
So the value is m = -6